The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cctc.201901698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Promoter Nature on Synthesis Gas Conversion to Alcohols over (K)MeMoS2/Al2O3 Catalysts

Abstract: The influence of the promoter nature and of a modifier in (K)(Me)MoS2/Al2O3 (Me=Fe, Co, Ni) catalysts on the conversion and selectivity of products of synthesis gas conversion to alcohols and jnl oxygenates was investigated. Relationships between promoter nature, hydrocarbon chain length and selectivity in the formed alcohols were established. Electronic structure of a promoter atom in an active site (AS) was found to strongly affect selectivity of alcohol formation. Promotion of the S‐edge by Fe, Co or Ni sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Enlightened by such a report, we deemed that the lower catalytic performances of Cat-OBC-1 compared with Cat-DAC-1 can be attributed to the agglomeration of the active phase; OBC-1 formed a higher agglomerate compared with DAC (see Figure 1 and Figure S2 ), thus increasing the rim sides and coupling the important sides of HAS (basal, corner, and surface sides). 55 57 Figure 5 b revealed that there is no clear correlation between temperature and total liquid yield. Moreover, the KCoMoS 2 catalysts supported powder ACs (Cat-DAC and Cat-OBC-1) yielded more total liquids than fiber ACs (Cat-TCA and Cat-AHM).…”
Section: Results and Discussionmentioning
confidence: 95%
“…Enlightened by such a report, we deemed that the lower catalytic performances of Cat-OBC-1 compared with Cat-DAC-1 can be attributed to the agglomeration of the active phase; OBC-1 formed a higher agglomerate compared with DAC (see Figure 1 and Figure S2 ), thus increasing the rim sides and coupling the important sides of HAS (basal, corner, and surface sides). 55 57 Figure 5 b revealed that there is no clear correlation between temperature and total liquid yield. Moreover, the KCoMoS 2 catalysts supported powder ACs (Cat-DAC and Cat-OBC-1) yielded more total liquids than fiber ACs (Cat-TCA and Cat-AHM).…”
Section: Results and Discussionmentioning
confidence: 95%
“…The primary product according to the carbide mechanism for the higher alcohol formation is an olefin which is rapidly hydrogenated to the corresponding alkane. One important parameter, related to higher alcohols formation from syngas is the chain growth probability, α, which is essential for calculations of the weight fraction of alcohols, W n, [4,5,28,29–31,33,34–37,42,44,48,52] Wnormaln/n=(1-α2)/α*αnormaln $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm W}{_{{\rm n}}}/{\rm n}=(1\hbox{-}{\rm \alpha} {^{2}})/{\rm \alpha} {^\ast}{\rm \alpha} {^{{\rm n}}}\ \hfill\cr}}$ …”
Section: Reaction Networkmentioning
confidence: 99%
“…Transformation of syngas to higher alcohols is currently under intensive research [2,4,5,23–57] and several reviews have been published rather recently covering the nature of active centers„ [1,54] and more specifically performance of Fe/Co catalysts and Co carbide nanocatalysts [59] . A simplified reaction scheme for syngas transformation over a bifunctional catalyst is shown in Figure 1 [40] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of catalytic synthesis of methanethiol, transition metal sulfides are generally considered to be the main active phase [10,11,14,[17][18][19][20]. Among them, MoS 2 -based catalysts promoted by alkali metals have potential application prospects because of their unique properties, such as sulfur resistance, not ease to coking and avoiding expensive deep desulfurization in industry, which have been also widely used in water-gas shift [21][22][23][24], syngas to higher alcohols [25][26][27][28][29][30], hydrodesulfurization [31][32][33][34] and hydrogenation [35][36][37][38]. The research results of active phase MoS 2 in these fields can also provide some reliable basis for the synthesis of CH 3 SH.…”
Section: Introductionmentioning
confidence: 99%